Perspectivas gerais sobre a preservação digital: uma abordagem a partir dos documentos digitais - CABRAL, Igor Eduardo da Costa (2024)
The research discusses digital preservation from the perspective of digital and digitized archival documents in their technological evolution, considering that such a focus is necessary to delimit the problem of digital preservation in Archivology. In this aspect, the general objective is to present digital preservation strategies from the perspective of digital and digitized archival documents. To satisfy the general objective, the follow-ing two specific objectives were achieved: The first consisted of conceptualizing digital documents and the second was describing digital preservation strategies. The meth-odology used was exploratory research of an unstructured nature with the approach of works by convergent authors on the topic, found in databases such as Google Acadêmico, SciELO and BRAPCI. The results obtained relate the applicability of digital preservation strategies and their consequences in each technological context, taking into account their historical contribution to memory and the possibility of the product being made available at low cost and easy access to the end user. Finally, it is con-cluded that just adopting a preservation strategy is not enough to achieve digital preservation; In this way, the improvement of free source software for digital preserva-tion is encouraged with the aim of reducing costs and wide use by virtual communities